2010
DOI: 10.1021/la1012507
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Si Nanopillar Arrays Fabricated by Colloidal Lithography and Catalytic Etching for Broadband and Omnidirectional Elimination of Fresnel Reflection

Abstract: Periodic Si nanopillar arrays (NPAs) were fabricated by the colloidal lithography combined with catalytic etching. By varying the size of colloidal crystals using oxygen plasma etching, Si NPAs with desirable diameter and fill factor could be obtained. The Fresnel reflection can be eliminated effectively over broadband regions by NPAs; i.e., the wavelength-averaged specular reflectance is decreased to 0.70% at wavelengths of 200-1900 nm. The reflectance is reduced greatly for the incident angles up to 70 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 36 publications
2
90
0
Order By: Relevance
“…As opposed to the top-down method, bottom-up fabrication of nanostructures is an enticing approach to fabricate nanostructures without using costly processes such as lithography and dry-etching. [ 5,17,22,32,51,63,64,[74][75][76][77] As an example, Fan et al reported ordered arrays of Germanium (Ge) dual-diameter Nanopillars (DNPLs) with different diameters at the tip and base fabricated inside self-organized anodic aluminum oxide (AAO) templates. Such DNPLs presented an impressive absorption of 99% of the incident light over a wavelength ranging from 300 to 900 nm with a thickness of only 2 µm.…”
Section: Brief Review Of Light Harvesting With Nanostructuresmentioning
confidence: 99%
“…As opposed to the top-down method, bottom-up fabrication of nanostructures is an enticing approach to fabricate nanostructures without using costly processes such as lithography and dry-etching. [ 5,17,22,32,51,63,64,[74][75][76][77] As an example, Fan et al reported ordered arrays of Germanium (Ge) dual-diameter Nanopillars (DNPLs) with different diameters at the tip and base fabricated inside self-organized anodic aluminum oxide (AAO) templates. Such DNPLs presented an impressive absorption of 99% of the incident light over a wavelength ranging from 300 to 900 nm with a thickness of only 2 µm.…”
Section: Brief Review Of Light Harvesting With Nanostructuresmentioning
confidence: 99%
“…4 shows that the reflectivities of the samples decreased compared to those of the bare plain c-Si cells in the UV-Vis wavelength range due to light scattering 16 and effective medium theory. 17 Incident light absorption can be improved by increasing the optical path length inside the c-Si solar cell via the light-trapping structure of Ag NPs. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Using these nanowires, both transverse-electric (TE) and transverse-magnetic (TM) reflectance remains below 0.1% for incident angles of up to 55° at 528 nm, exhibiting superior omnidirectionality polarizationinsensitive AR properties. [46] …”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[147] For all of these studies, no V OC or fill factor losses were observed. [46,120,[148][149][150] …”
Section: Nanostructure Layers On the Solar Device Exteriormentioning
confidence: 99%